Finasteride Enhances Stem Cell Signals of Human Dermal Papilla Cells - RATTANACHITTHAWAT, NAPAPAT (In Vivo, 2019)
Background/Aim: Finasteride (FN) has been widely used to treat androgenetic alopecia (AGA). This study aimed at exploring the effect of FN on DP stem cell properties. Materials and Methods: Effect of FN on stem cell properties was tested in a DP cell line and 2 human primary DP cells (HDPCs1 and HDPCs2). Cell toxicity and growth were analyzed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The aggregation behavior was observed by phase-contrast microscopy and a scanning electron microscope (SEM). Effects of FN on cell signaling were determined by western blotting and immunocytochemistry. Results: Treatment of DPCs with FN was able to significantly increase their aggregation behavior and the expression of stem cell transcription factors Nanog and Sox-2, when compared to the non-treated control. FN up-regulated stem cell regulatory proteins through the activation of protein kinase B (AKT), β-catenin, and integrin-β1. Conclusion: FN had an interesting biological effect on stem cell induction. These findings support the use of this drug for hair loss control and the development of regeneration approaches.